ANALISIS RESIKO PENDAPATAN USAHATANI BAWANG MERAH DI DESA TUNGKU JAYA KECAMATAN SOSOH BUAY RAYAP KABUPATEN OGAN KOMERING ULU (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2018)
This study aims to calculate the income of farmers from onion farming in Tungku Jaya Village, Sosoh Buay Termap District, Ogan Komering Ulu District. To analyze the risk of onion farming in Tungku Jaya Village, Sosoh Buay Termal Sub-district, Ogan Komering Ulu District. The research method used is case study method. Case study method is a method of research done because the farm is only in one place and no other place. Data processing method is done using the formula of income and income risk. After the calculation showed that onion farming in Tungku Jaya Village Sosoh Buay Termap Sub-district of Ogan Komering Ulu Regency generated an average income of Rp.71,894,700. From the calculation, we can know the amount of standard deviation of Rp.3.198,211. coefficient of variation obtained 0,0000444847 which means CV < 0,5 then the value of L > 0, then the farm will have a chance will always get a profit.